Treatment of Children with Diffuse Intrinsic Pontine Gliomas with Chemoradiotherapy Followed by a Combination of Temozolomide, Irinotecan, and Bevacizumab. (1st October 2013) - Zaky, Wafik; Wellner, Michael; Brown, Robert J.; Blüml, Stefan; Finlay, Jonathan L.; Dhall, Girish
<x xml:space="preserve">Abstract</x> Background: Diffuse intrinsic pontine gliomas (DIPG) are inoperable and highly resistant tumors to chemotherapy and irradiation. DIPG has the worst prognosis among all pediatric brain tumors and the overwhelming majority of patients die within 6–18 months after diagnosis. Methods: We retrospectively reviewed the charts of six DIPG patients treated with chemoradiotherapy (daily carboplatin and oral etoposide in five patients and temozolomide in one patient) followed by maintenance chemotherapy consisting of irinotecan, temozolomide, and bevacizumab at our institution between January 2007 until December 2007. Results: Event-free survival (EFS) and overall survival (OS) were 10.4 ± 3.08 and 14.6 ± 3.55 months, respectively. Side effects in the patients included hypertension in two, abdominal cramping and diarrhea in four, and neutropenia in five patients. Conclusions: This augmented regimen was associated with increased but tolerable toxicity and a modest increase in EFS and OS when compared with published literature in patients with DIPG (median EFS and OS of 6.1 and 9.6 months, respectively). More effective therapies are desperately needed.